Minimal requirements for reverse polymerization and tRNA repair by tRNAHis guanylyltransferase. Issue 4 (4th May 2018) - Desai, Riddhi; Kim, Kunmo; Büchsenschütz, Hanna C.; Chen, Allan W.; Bi, Yumin; Mann, Mitchell R.; Turk, Matthew A.; Chung, Christina Z.; Heinemann, Ilka U.
ABSTRACT: tRNA His guanylyltransferase (Thg1) has unique reverse (3'-5') polymerase activity occurring in all three domains of life. Most eukaryotic Thg1 homologs are essential genes involved in tRNA His maturation. These enzymes normally catalyze a single 5' guanylation of tRNA His lacking the essential G −1 identity element required for aminoacylation. Recent studies suggest that archaeal type Thg1, which includes most archaeal and bacterial Thg1 enzymes is phylogenetically distant from eukaryotic Thg1. Thg1 is evolutionarily related to canonical 5'-3' forward polymerases but catalyzes reverse 3'-5'polymerization. Similar to its forward polymerase counterparts, Thg1 encodes the conserved catalytic palm domain and fingers domain. Here we investigate the minimal requirements for reverse polymerization. We show that the naturally occurring minimal Thg1 enzyme from Ignicoccus hospitalis (IhThg1), which lacks parts of the conserved fingers domain, is catalytically active. And adds all four natural nucleotides to RNA substrates, we further show that the entire fingers domain of Methanosarcina acetivorans Thg1 and Pyrobaculum aerophilum Thg1 (PaThg1) is dispensable for enzymatic activity. In addition, we identified residues in yeast Thg1 that play a part in preventing extended polymerization. Mutation of these residues with alanine resulted in extended reverse polymerization. PaThg1 was found to catalyze extended, template dependent tRNA repair, adding up to 13 nucleotides to a truncated tRNA His substrate. Sequencing results suggest that PaThg1 fully restored the near correct sequence of the D- and acceptor stem, but also produced incompletely and incorrectly repaired tRNA products. This research forms the basis for future engineering efforts towards a high fidelity, template dependent reverse polymerase.